Barriers and Facilitators to Implementing Project ECHO in Malaysia During the COVID-19 Pandemic. (September 2022) - Walters, Suzan M.; Li, Wong Pui; Saifi, Rumana; Azwa, Iskandar; Syed Omar, Sharifah Faridah; Collier, Zachary K.; Amir Hassan, Asfarina Binti; Haddad, Marwan S.; Altice, Frederick L.; Kamarulzaman, Adeeba; Earnshaw, Valerie A.
Objective: In Malaysia, HIV is concentrated among key populations who experience barriers to care due to stigma and healthcare discrimination. The COVID-19 pandemic has increased barriers to healthcare. Project ECHO (Extension for Community Healthcare Outcomes) is a transformative tele-education strategy that could improve HIV prevention and treatment.Methods: Practicing physicians who were aged 18 years or older and had internet access participated in asynchronous online focus groups.Results: Barriers to Project ECHO were conflicting priorities, time constraints, and technology. Facilitators included content and format, dedicated time, asynchronized flexible programming, incentives, and ensuring technology was available.Conclusion: Project ECHO is a promising intervention that can increase physicians' knowledge and skill set in specialty medicine during the COVID-19 pandemic. Interventionists in Malaysia in particular, but also in general, should consider these barriers and facilitators when developing Project ECHO as they may aid in developing a more robust program and increase participation.